2003
DOI: 10.1182/blood-2003-05-1383
|View full text |Cite
|
Sign up to set email alerts
|

VH mutation status and VDJ rearrangement structure in mantle cell lymphoma: correlation with genomic aberrations, clinical characteristics, and outcome

Abstract: Immunoglobulin variable heavy chain gene (V H ) mutation status and VDJ rearrangement structure were analyzed in 141 patients with mantle cell lymphoma (MCL) and correlated with biologic and clinical characteristics; 29% of the MCLs displayed mutated V H using a 98% germline homology cutoff. Striking differences occurred in the V H mutation subgroups with respect to the use of specific V genes. Rearrangements involving V4-34 and V3-21 were almost exclusively unmutated, whereas rearrangements using V4-59 and V3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
103
1
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(125 citation statements)
references
References 44 publications
10
103
1
11
Order By: Relevance
“…24,25 In our studies, however, ZAP-70 was detected in only 13% mantle cell lymphoma cases. We also detected low level ZAP-70 protein expression in Mino, a mantle cell lymphoma cell line.…”
Section: Zap-70 In Hodgkin Lymphomascontrasting
confidence: 76%
“…24,25 In our studies, however, ZAP-70 was detected in only 13% mantle cell lymphoma cases. We also detected low level ZAP-70 protein expression in Mino, a mantle cell lymphoma cell line.…”
Section: Zap-70 In Hodgkin Lymphomascontrasting
confidence: 76%
“…Similar findings were reported by other studies, with V H 3-21, V H 4-59 and V H 4-34 being most commonly implicated. 15,18 In our study, we also identified a strong bias for V H 4-59, but we identified V H 1-69 and V H 3-74 as the most frequent utilized V H regions, neither of which were highly represented in the previous studies. These discrepancies may be attributed to methodological differences, as described above.…”
Section: Discussionsupporting
confidence: 43%
“…We also have considered the possibility that different IGH primers may have bias toward amplifying different V H regions. Lastly, all of the four previous large studies were from European centers, [15][16][17][18] and we cannot exclude the possibility that the North American population (as in this study) may have different characteristics than their European counterparts.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations